2016
DOI: 10.1038/srep19395
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a novel in vitro model of stratified epithelial wound healing with barrier function

Abstract: The repair of wounds through collective movement of epithelial cells is a fundamental process in multicellular organisms. In stratified epithelia such as the cornea and skin, healing occurs in three steps that include a latent, migratory, and reconstruction phases. Several simple and inexpensive assays have been developed to study the biology of cell migration in vitro. However, these assays are mostly based on monolayer systems that fail to reproduce the differentiation processes associated to multilayered sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Our figures are therefore of a similar order of magnitude, although lower, possibly as we were imaging ex-vivo samples at 25°C instead of in vivo cornea at 37°C and imaged close to an almost closed wound. Indeed, our measured migration rates are closer to those reported for similar in vitro reepithelialization cell migration studies in rabbit (10 − 16 µm.h −1 [34]). Our algorithm was validated by comparing with manual tracking of 200 voxels in cells on successive images.…”
Section: Slow Dynamics: Corneal Wound Healing Imagingsupporting
confidence: 88%
“…Our figures are therefore of a similar order of magnitude, although lower, possibly as we were imaging ex-vivo samples at 25°C instead of in vivo cornea at 37°C and imaged close to an almost closed wound. Indeed, our measured migration rates are closer to those reported for similar in vitro reepithelialization cell migration studies in rabbit (10 − 16 µm.h −1 [34]). Our algorithm was validated by comparing with manual tracking of 200 voxels in cells on successive images.…”
Section: Slow Dynamics: Corneal Wound Healing Imagingsupporting
confidence: 88%
“…At confluence, live/dead staining was performed with a staining kit (Life Technologies Corporation, Oregon, USA), where cells were double-stained by calceinacetoxymethyl (Calcein AM) and ethidium homodimer-1 (EthD-1). On live culture, to promote stratification after confluence, the media was changed to DMEM/Ham's F-12 media (Corning, VA, USA) supplemented with 10% newborn calf serum and 10 ng/ml EGF, and cultured for 7 days, as reported previously [49]. Afterwards, phase contrast images were taken with 10x objectives using an inverted microscope (Nikon Eclipse TS100, Nikon Instruments Inc.; Melville, NY).…”
Section: Human Corneal Epithelial Cells (Hcec)-mentioning
confidence: 99%
“…Thus, the development of 3D models that allow for the study of corneal wound healing would provide important advantages. Gonzalez-Andrades et al established an in vitro model of the cornea with a barrier function that is useful for studying wound healing [ 112 ]. With the same purpose of assessing corneal wound healing, McKay et al reported the development of a coculture system of human corneal epithelial cells and corneal stromal fibroblasts that secrete their own extracellular matrix [ 113 ].…”
Section: Three-dimensional In Vitro Models Of Anterior Eye Tissuesmentioning
confidence: 99%